Squaramide-substituted calix[4]pyrrole: Synthesis and ion binding studies. Issue 36 (6th September 2019) - He, Ying-Chun; Ren, Zhen-Xing; Zhao, Xue-Feng; Zhang, Yong-Bin; Wang, Jun-Hong; Chao, Jian-Bin; Wang, Meng-Liang
Abstract: Squaramide-substituted calix[4]pyrrole2 was synthesized and its anion-binding properties were investigated. On the basis of UV spectroscopy, 1 H NMR spectroscopic and computational DFT model analyses, compared with the parent calix[4]pyrrole1, compound2 shows significantly enhanced binding affinities for anions in CH2 Cl2, and it was concluded that this increase in affinity is ascribed to participation of the squaramide unit in anion binding. Graphical abstract: Image 1 Highlights: Squaramide-substituted calix[4]pyrrole 2 has been synthesized and unambiguously characterized by NMR and HRMS spectrum. On the basis of UV spectroscop and 1H NMR analyses, calix[4]pyrrole 2 shows strong binding affinities for anions. It was concluded that the increase in aﬃnity is ascribed to participation of the squaramide unit in anion binding.